Corruption in the Study of Law and Human Rights - Pricilia Ryana; Aisy Idzati (Lex Scientia Law Review, 2018)
It seems that the relationship between Corruption and Human Rights has not been widely discussed among academics and practitioners, there is not even much literature or textbooks on this subject. This may be due to the fact that the substance of corruption or criminal acts of corruption does not directly mention the substantive relationship between corruption and human rights. The phenomenon of corruption has resulted in poverty, low levels of education and health, and poor public services. And as a result of corruption, suffering is always experienced by the community, especially small communities who are below the poverty line.